1985
DOI: 10.1002/med.2610050405
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the design of angiotensin‐converting enzyme inhibitors

Abstract: Orally-active angiotensin-converting enzyme inhibitors are rapidly establishing themselves in the therapy of hypertension and congestive heart failure. Concerted efforts in a number of laboratories have now led to the discovery or synthesis of an unparalleled variety of potent inhibitors. The manner in which several of these inhibitors bind to ACE is beginning to be understood. It is hoped that some of the insights to be derived from the SAR and structural studies done with ACE inhibitors will be applicable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
165
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(175 citation statements)
references
References 137 publications
9
165
0
1
Order By: Relevance
“…However, the use of different methods and their associated modifications to test ACE inhibitory capacity makes difficult the direct comparison of IC 50 values from different studies when some reports do not detail the number of enzyme units used in the inhibition analysis or do not include an IC 50 value for an ACE inhibitory standard such as Captopril® (Murray, Walsh & FitzGerald, 2004). As an example, the dipeptide AlaPro has been reported with IC 50 values ranging from 29 to 230 M (Wyvratt & Patchett, 1985;Ichimura, Hu, Aita & Maruyama, 2003;Fuglsang, Nilsson & Nyborg, 2003).…”
Section: Ace Inhibitory Activity Of Synthetically Derived Peptidesmentioning
confidence: 99%
“…However, the use of different methods and their associated modifications to test ACE inhibitory capacity makes difficult the direct comparison of IC 50 values from different studies when some reports do not detail the number of enzyme units used in the inhibition analysis or do not include an IC 50 value for an ACE inhibitory standard such as Captopril® (Murray, Walsh & FitzGerald, 2004). As an example, the dipeptide AlaPro has been reported with IC 50 values ranging from 29 to 230 M (Wyvratt & Patchett, 1985;Ichimura, Hu, Aita & Maruyama, 2003;Fuglsang, Nilsson & Nyborg, 2003).…”
Section: Ace Inhibitory Activity Of Synthetically Derived Peptidesmentioning
confidence: 99%
“…It is worth noting that the potency of our best NS3/4A inhibitor (2 µM) is equivalent to the potency (IC 50 ) 4.9 and 2.4 µM, respectively) of N-carboxyalkyl or N-carboxymethyl dipeptide inhibitors of ACE lacking the P 1 side chain (46). Introduction of the proper P 1 side chain in the collected product leads to enalaprilat, and this is also the current direction of our design for NS3/4A.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to binding into the active site, ACE inhibitors extended into the S 1 ′ and S 2 ′ subsites. Occupancy also of the S 1 subsite, although not strictly required for activity, greatly improved potency (46).…”
Section: Discussionmentioning
confidence: 99%
“…Enalapril maleate is a monoethyl ester prodrug of the diacid enalaprilat. This prodrug (enalapril maleate) needs to undergo deesterification in vivo to produce its active form, enalaprilat (Wyvratt & Patchett, 1985). Studies in man indicate that absorption of enalapril maleate (61% oral availability) is rapid (peak plasma levels between 0.5-1.5 h after administration) and that enalapril maleate/enalaprilat is recovered intact (94%) from urine and faeces (apart from the bioactivation which is post-absorptive) .…”
Section: Resultsmentioning
confidence: 99%
“…The effects of enalapril maleate and lisinopril are both longer lasting than the effects of the less stable captopril . The structures of the first three orally-active ACE inhibitors (captopril, enalapril maleate and lisinopril) are similar or analogous to the dipeptide Ala-Pro (Wyvratt & Patchett, 1985) which is the C-terminal dipeptide of bradykinin-potentiating peptide Sa (BPP5a), a potent inhibitor of ACE activity isolated from snake venom (Cheung et al, 1980;Wyvratt & Patchett, 1986). Studies in rat jejunum using the single-pass perfusion method have suggested that the significant levels of absorption of these three ACE inhibitors across the intestinal epithelial wall is due to transport via the intestinal di/tripeptide carrier (Hu & Amidon, 1988;Friedman & Amidon, 1989a,b).…”
Section: Resultsmentioning
confidence: 99%